The Relationship between Exercising of Shareholders’ Rights and the Performance of Firms listed at the Nairobi Securities Exchange - Maina, Dr. Edward Kandiru (International Journal of Scientific Research and Management (IJSRM), 2018)
The continued decline in performance of firms listed in the Nairobi Securities Exchange (NSE) has lately become a source of concern to both the country’s policy makers and researchers. Already, reports from the Kenyan government reveal that the decline in performance is becoming an impediment to the country’s realization of Vision 2030 as the dwindling performance is leading to lower economic development and loss of jobs. This study examines the relationship between exercising of shareholders’ rights and the performance of firms listed in the NSE for the period 2011-2015. The study is anchored on the shareholder theory. The study population comprises all 60 companies listed in NSE in the stated period. The study uses descriptive research and correlational research designs. Both primary and secondary data are obtained from the 60 Chief Executive Officers of the corporations or their representatives. Descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation and multiple regression) are used to analyze the data. The study finds that there is a statistically significant relationship between shareholders exercising their rights and performance of firms listed at the Nairobi Securities Exchange. The hypothesis that shareholders exercising their rights has no significant relationship with performance of firms listed at the NSE (p